349 Early safety and efficacy of a phase 1/2 open-label, multi-center trial of SNS-301 added to pembrolizumab in patients with advanced squamous cell carcinoma of the head and neck (SCCHN). (9th November 2020) - Algazi, Alain; Smith, William; Panella, Timothy; Shin, Dong; Fjaellskog, Marie-Louise; Celebi, John; Drumheller, Alice; Campbell, Jean; Pierce, Robert; Guarino, Michael
Abstract : Background: Efficacy of anti-PD-1 therapy is attributed to the presence of infiltrating antigen-specific CD8+ T-cells. Despite the success of anti-PD-1 therapy, many patients with SCCHN present with immune desert or immune excluded tumors and only 13–18% of patients achieve tumor reductions. Given this low response rate, it is imperative to combine agents that generate or expand anti-tumor T cells, such as vaccines, with anti-PD-1 therapies. SNS-301 is a first-in-class, bacteriophage-based immune activating agent targeting human aspartate β-hydroxylase (ASPH), a tumor associated antigen overexpressed in multiple tumor types. SNS-301 is a self-adjuvanted vaccine consisting of λ-bacteriophage engineered to express an immunogenic fragment of ASPH fused to the phage gpD coat protein, previously shown to be well tolerated and generate an immune response (Phase 1, NCT03120832 ). The objectives of this trial are to evaluate safety, immunogenicity and preliminary efficacy of SNS-301 in combination with pembrolizumab in patients that did not achieve tumor reductions on anti-PD-1/PD-L1 therapy alone. Methods: The study consists of an initial safety-run-in followed by a two-stage design. SNS-301 is delivered intradermally in addition to pembrolizumab in up to 30 patients with locally advanced unresectable or metastatic/recurrent SCCHN. Patients must have actively received anti-PD-1 therapy for ≥12 weeks, with a best response of stable disease (SD) or unconfirmed progressive disease (PD) per iRECIST. Patients provide pre, on-treatment and biopsies at PD (optional) to characterize the tumor microenvironment using Nanostring TM, multiplex immunohistochemistry, and correlate with clinical outcomes. Blood samples are collected to evaluate T cell responses using flow cytometry, ELISA, ELISPOT. Results: As of July 23, 2020, 9 patients were enrolled. Median duration of ongoing anti-PD therapy was 37 weeks (range 20–101). The combination was well-tolerated with no DLTs and mostly Grade 1–2 unrelated adverse events. Two Grade 3 events were reported: hypertension (not related) and dehydration (related), the later reported as serious adverse event. Of seven patients eligible for efficacy analysis, one patient with PD-L1 negative disease had a partial response with a reduction of 29% at week 6 with deepening of the response to 43% at week 12 and one patient with progressive disease at study entry had stabilization of disease at week 6 and 12. Another two patients had stable disease for 30+ weeks and three patients had PD. Additional efficacy and immunological analyses are ongoing. Conclusions: Early data show that the combination of SNS-301 and pembrolizumab has manageable toxicity and capacity to achieve long-term disease stability and objective tumor responses. Trial Registration: NCT04034225 Ethics Approval: This study has been approved by WIRB (20190628) as well as several institutional IRBs.